Wyrażenia algebraicznee napiszcie ;)

a) 3x-2y-6x-2y+3x=
b) 6ab-4a+3b+5ab+a-3b-8ab=
c) -2a-b+ab2 (do kwardatu) +3 + -4 +b-a2b+2a=
d) -x-6+xy-y-x-6+xy-y=
e) 2x+3y+3xy+x2-2x-3y-4xy =
f) 2a+(3a-7)=
g)5x-(y-2x)=
h) (4x+2xy+3) - (-5x+2xy-6)=

Dziękii !

3

Odpowiedzi

2010-03-25T16:23:24+01:00
A) 3x-2y-6x-2y+3x=-4y
b) 6ab-4a+3b+5ab+a-3b-8ab=3ab-3a
c) -2a-b+ab2 (do kwardatu) +3 + -4 +b-a2b+2a=2ab-1
d) -x-6+xy-y-x-6+xy-y=-2x-12+2xy-2y
e) 2x+3y+3xy+x2-2x-3y-4xy=2x-xy
f) 2a+(3a-7)=5a-7
g)5x-(y-2x)=7x-y
h) (4x+2xy+3) - (-5x+2xy-6)=(4x+2xy+3)+5x-2xy+6=9x+9
1 5 1
2010-03-25T16:24:20+01:00
A) 3x-6x+3x-2y-2y=-4y
b) = 3ab-3a
c) =4a+b(kwadrat)+4a(kwadrat)B(kwadrat)+3+(-4)+b-2ab+2a=6a+b(kwadrat)+4a(kwadrat)B(kwadrat)-1+b-2ab
d) =-2x-12+2xy-2y
e) = 2x-1xy
f) = 5a-7
g) = 5x-y+2x= 7x-y
h) 4x+2xy+3-5x-2xy+6= -1x+9

chyba dobrze ;)
2010-03-25T16:28:10+01:00
A) 3x-2y-6x-2y+3x= -4y
b) 6ab-4a+3b+5ab+a-3b-8ab= 3ab-3a
c) -2a-b+ab2(do kwadratu)+3+(-4) +b-a2b+2a= ab2(do kwadratu)-1-a2b
d) -x-6+xy-y-x-6+xy-y=-2x-12-2y
e) 2x+3y+3xy+x2-2x-3y-4xy = 2x-1xy
f) 2a+(3a-7)= 2a+3a-7=5a-7
g) 5x-(y-2x)=5x-y+2x= 7x-y
h) (4x+2xy+3) - (-5x+2xy-6)=4x+2xy+3+5x-2xy+6= 9x+9